Evidence-based implementation of normal childbirth: what are the obstacles? (qualitative study) - Rizki Amalia; Moch. Hakimi; Herlin Fitriani (Journal of Health Technology Assessment in Midwifery, 2020)
Evidence-based is a very effective strategy to improve the quality of midwifery services. One of the most frequently problems faced is the gap between midwifery practices that are in accordance with the procedures (based on evidence-based) with clinical care practices that occur in the clinic. The purpose of this study was to explore in-depth the obstacles to the implementation of evidence-based normal childbirth, which are the position of delivery, monitoring and documenting delivery by using partographs in the Independent Practice of Midwives of Gunungkidul District, Yogyakarta.This research was a qualitative research with a phenomenological descriptive approach. The participants of this study were midwives who had the Independent Midwife Practice (PMB) consisting of 7 informants. Participant selection in this study used a purposive sampling technique with convenience sampling and identification of obstacles used was the Consolidated Framework for Implementation Research (CFIR). Data collection used was semi-structured interviews and observations. Data analysis used was a thematic analysis.The interview and observation of delivery assistance is done at the Independent Midwife Practice Center (PMB). The position of delivery that was often used by patients was lithotomy and left slant, and the application of evidence-based monitoring and documentation using partograph was still not optimal. This was because there were several obstacles in its application, which were obstacles from patients, families, midwives, and obstacles from the organization. The impact of these obstacles was that it can reduce the quality of obstetric care in patients according to evidence-based. The evaluation of clinical practice based on evidence-based by the organization and the existence of feedback from patients to midwives are expected to improve the quality of service to patients.